Transition metal titanium (Ti) doped LaFeO3 nanoparticles for enhanced optical structural and magnetic properties - Sasikala, C.; Durairaj, N.; Baskaran, I.; Sathyaseelan, B.; Henini, M.; Manikandan, E. (Elsevier, 2017)
A series of LaFe1−xTixO3 (x = 0.0, 0.2, 0.4, 0.6 and 0.8) nanoparticles have been successfully synthesized by simple co-precipitation technique. The synthesized samples (calcined at 800° C/3hr) were characterised for structural, optical and magnetic properties. Structural phase formation of the crystal shows orthorhombic planes of these samples phases. The average crystallite size (Dc) is decreasing with a dopant and found to be varying between ∼ 9 and 25 nm. Tailored surface morphology was analyzed using scanning electron microscope (FESEM) and transmission electron microscopes (TEM) with selected area electron diffraction pattern (SAED) also confirms the evolution of orthorhombic phases. Diffuse reflectance spectra (DRS) are recorded to evaluate the variation of optical band gap (Eg) upon titanium doping into the LaFeO3 system. The obtained results attributed that Eg values are increasing with dopant altering between 2.05 and 2.61 eV. The metal oxide (M - O) stretching vibrations and few functional groups are detected from infrared spectra (IR). The weak ferromagnetic behaviour is observed from hysteresis loop behaviour. Additionally, the large hysteresis loop behaviour induces no saturation up to 15 kOe in nanoparticles coercivity (Hc) and anisotropy constants (K1) are eventually decreasing with ‘x’ values.